Fauna i flora w staropolskich opisach Orientu (wybrane przykłady) - Kuran, Michał; Agnieszka Gralak (Motywy fauny i flory w literaturze i kulturze, 2018)
The article presents a literary picture of oriental flora and fauna outlined in chosen texts written in Polish from 16th to 17th century. The material is divided into two groups: first consists of primary writings, written by former slave, traveller and diplomats, the second are secondary writings created by diarist and author of handbook for potential slaves. Analyzed were following texts: The Conversation With a Turkish about a Christian Faith by Bartłomiej Georgiewicz, About the Beginnings, Arguments, Gallantry, the Knight and Home Affairs of the Famous Lithuanian Nation by Maciej Stryjkowski, Peregrination or Pilgrimage to the Holy Land by Mikołaj Krzysztof Radziwiłł, The Prevailing Legation by Samuel Twardowski, The Chronicle of Sarmatian Europe by Aleksander Gwagnin and The History of Turkey by Marcin Paszkowski. Worth considering were criteria of choice of described plants and animals (known — familiar and unknown — exotic; functioning wild or cultivated or breeded; existence or lack of existence of fantastic creatures and their function in text), differences in outlook of flora and fauna from the point of view of slave, traveller and diplomat and according to the image established in the secondary writings. Important was the range of author’s observations: whether it presented panorama or single object; whether it was conducted on land or from the sea or from the river. The way of description — the unknown they tried to present by means of comparisons to the known one. A description technique was applied that affects the senses of sight, hearing and smell. The observation was conducted over a narrative way of capturing a static object or moving to a static or remaining in move subject.